2020
DOI: 10.4097/kja.19479
|View full text |Cite
|
Sign up to set email alerts
|

Rhomboid intercostal and subserratus plane block -a case series-

Abstract: Background: The Rhomboid intercostal and Subserratus plane (RISS) block is a new interfascial block that has shown promising results for abdominal and thoracic surgeries. Our objective was to describe improved analgesia and dermatomal coverage within the patients who received bilateral ARISS blocks after major abdominal surgery. Case: Twenty-one patients who underwent abdominal surgery received the rhomboid intercostal component of the block at the level of T5 to T6 and the subserratus component block was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…The main causes of early pain after laparoscopic cholecystectomy are peritoneum and abdominal wall distension due to pneumoperitoneum and somatic pain at the trocar insertion site(s) [ 4 , 5 ]. Effective use of truncal blocks, such as the erector spinae plane or quadratus lumborum block, has been demonstrated in postoperative pain management in laparoscopic cholecystectomy [ 6 - 8 ]. The rhomboid intercostal and subserratus plane (RISS) block provides analgesia from the third to the 12th thoracic dermatomes and has been used in postoperative pain management for thoracic surgeries [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main causes of early pain after laparoscopic cholecystectomy are peritoneum and abdominal wall distension due to pneumoperitoneum and somatic pain at the trocar insertion site(s) [ 4 , 5 ]. Effective use of truncal blocks, such as the erector spinae plane or quadratus lumborum block, has been demonstrated in postoperative pain management in laparoscopic cholecystectomy [ 6 - 8 ]. The rhomboid intercostal and subserratus plane (RISS) block provides analgesia from the third to the 12th thoracic dermatomes and has been used in postoperative pain management for thoracic surgeries [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Effective use of truncal blocks, such as the erector spinae plane or quadratus lumborum block, has been demonstrated in postoperative pain management in laparoscopic cholecystectomy [ 6 - 8 ]. The rhomboid intercostal and subserratus plane (RISS) block provides analgesia from the third to the 12th thoracic dermatomes and has been used in postoperative pain management for thoracic surgeries [ 7 , 8 ]. Although it is used for postoperative analgesia after upper abdominal surgery, there have been no adequate studies investigating the use of RISS blocks in laparoscopic cholecystectomy [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rhomboid intercostal block (RIB) is a novel block that may be used for several indications such as thoracic procedures and myofascial pain [ 1 , 2 ]. It may be performed for open thoracotomy [ 3 ]; however, more information is needed for other thoracic procedures.…”
mentioning
confidence: 99%
“…We have read with great interest the article on rhomboid intercostal and subserratus block by Elsharkawy et al [ 1 ]. They have reported that rhomboid intercostal and sub-serratus block helps effectively manage pain in patients after major abdominal surgeries.…”
mentioning
confidence: 99%